Portrait of Poverty in Palu and Paku, Usaha Samad, and Si Sapar by Utuy Tatang Sontani: Literary Sociology - Wulanjari, Raras Cynantia (J-LELC: Journal of Language Education, Linguistics, and Culture, 2024)
This research analyzes the portait of poverty depicted in three short stories of Utuy Tatang Sontani: “Palu and Paku, “Usaha Samad”, and “Si Sapar”. The focus of this research is social conflict, injustice, and the interaction between the characters in the context of poverty. The short story “Palu and Paku” tells about the life of a pedicab driver who faces a challenge to maintain his dignity in the midst of difficult economic conditions. “Samad’s Effort” tells the story of the persistence and struggle of a street vendor trying to escape poverty. And in “Si Sapar”, Utuy talks about the poverty of street children and how poverty can affect a person’s life from an early age. This research deeply discusses the depiction of poverty in Utuy Tatang Sontani’s literary works and how literature functions as a social reflection that reflects social reality. The findings in this study are expected to contribute to the development of literary sociology and raise awareness of social issues in literature and society in general, especially regarding poverty.